Expressões idiomáticas não são processadas como metáforas - Lais Marçal de Oliveira (2024)
This dissertation presents a study on idiomatic constructions (IC) in Brazilian Portuguese (PB), contrasting them with metaphorical constructions (MC). IC’s are expressions in which the meaning does not derive from the meaning of each individual item that composes them. They are conventional constructions widely used by language users. Linguistic studies, from a traditional perspective, consider IC’s as peripheral structures of the language that, due to their idiosyncratic nature, pose theoretical problems. The tradition also tends to comprehend IC’s as metaphorical constructions (Riva, 2009; Xatara, 1995, 1998, and others). However, following the reasoning ouTRined in Fulgêncio and Ciríaco (2018), the experimental hypothesis raised by this research is that idiomatic constructions are not processed as metaphorical constructions, specifically new metaphorical constructions (NMC), which demand an active engagement from users to construct meaning during interaction. Thus, through a self-paced reading test, the aim is to answer the question: Do IC’s have a metaphorical nature? Reading times (RT) in target and subsequent passages of experimental sentences at three condition levels will be analyzed: idiomatic constructions (IC), conventional metaphorical constructions (CMC), and new metaphorical constructions (NMC). The overall objective of this study is, therefore, to contribute to the theoretical description of idiomatic constructions in PB and to experimentally verify the processing status of these constructions. The specific objectives are: (i) to describe ICs based on the theoretical framework of usage-based linguistics; (ii) to analyze the results of the self-paced reading test in light of the aforementioned approach and the theories of metaphor that understand it as a cognitive process. From the analysis of the data and discussions, differences in reading time were found indicating a higher cognitive cost of new metaphorical constructions compared to idiomatic constructions in the subsequent passage. Additionally, processing differences were found indicating a lower cognitive cost of conventional metaphorical constructions compared to idiomatic constructions. The study also points out differences between the two types of analyzed metaphors: CMC and NMC, with longer reading times for new metaphors. Furthermore, it was possible to describe ICs in an approach that accommodates their irregular behavior, understanding them as constructions that pair a form strongly associated with an idiomatic meaning.